Context Based Querying of Dynamic and Heterogeneous Information Sources - Orsi, G (2011)
The proliferation of freely-accessible data-intensive websites, the growing availability of pervasive and mobile applications, as well as initiatives for open-accessible linked data in the Web, provided the users with potential sources of valuable information. These data also represent new business opportunities for industries, while their processing and management is a rich research field for academics. In addition, pervasiveness and mobility make information available everywhere and at any time; therefore, user-centred, dynamic and on-the-fly integration of heterogeneous becomes extremely useful in practical situations such as mobile data management, in particular with devices as tablets, pads and smartphones. We present a methodology and a set of technologies for ontology-driven, context-aware data-integration systems capable of seamlessly handling heterogeneous and dynamic data sources in a dynamic environment where the possibly mobile, transient and evolving data sources are not known in advance. In such Nomadic Data-Integration Systems (N-DIS), query answering is driven by an ontology and the context is used to formally represent the situations in which the users or the applications need to operate. In our work, we re-think query-answering techniques coming from description logics and database theory, and we apply them to an evolving scenario, composed by heterogeneous data sources with the additional constraint of the context-based personalisation of queries and, as a consequence, of their answers. The concept of N-DIS and the corresponding design methodology has been applied to various application fields such as decision support for medical-emergency situations, Semantic-Web meta-data management, Semantic Search and pervasive advertisement, with promising results.